Strategi Rekrutmen Dan Seleksi Tenaga Kerja Freelance Di Bidang Jasa Wedding Organizer Di Kota Magelang - Ari Tri Setiyowati; Hanung Eka Atmaja (Lembaga Pengembangan Kinerja Dosen, 2023)
The problem that arises in the recruitment of freelance workers is the lack of careful recruitment planning, which results in failure to achieve company goals. In addition, it is common to find freelance workers who lack motivation or enthusiasm in carrying out their duties, thus hindering the achievement of the desired goals. The research method used is descriptive research and qualitative research. Collecting data by surveying research objects and direct interviews with several directors of wedding organizers in the city of Magelang. Recruitment and selection strategies for freelance workers in the field of wedding organizer services in Magelang City need to be carried out carefully to obtain a workforce that fits the company's needs. In this discussion, we have identified several strategies that can be implemented, including building networks with related parties, creating clear job descriptions and qualifications, using online recruitment platforms, adopting selection tests and interviews, and verifying references and work experience. Overall, the strategy of recruiting and selecting freelance workers in the field of wedding organizer services in the City of Magelang is very important to ensure companies can obtain a quality workforce that suits their needs. By implementing the strategies that have been discussed, companies can build a team of freelance workers who are reliable, creative and able to provide the best service to clients.